Evaluation of the use of a copper and zinc chelate in the treatment of cows affected by digital dermatitis - Moura, R.B.R. [UNESP]; Teodoro, P.H.M. [UNESP]; Silva, J.R.B. [UNESP]; Mendonça, A.P.A. [UNESP]; Cestari, H. [UNESP]; Rodrigues, C. A. [UNESP] (FapUNIFESP (SciELO), 2025)
ABSTRACT The aim of this study was to evaluate the effectiveness of copper-zinc chelate spray in the treatment of digital dermatitis (DD). 39 limbs with DD injuries from 36 dairy cows were included, divided into three groups: group 1 treated with spray alone, group 2 with spray and bandage, and group 3 with spray and bandage only in the first 3 days. The cows were evaluated for locomotion score and qualitative analysis of the lesions on D0 (identification of the lesion and start of treatment), D3 (third day of treatment), D7 (seventh day of treatment) and D10 (tenth and last day of treatment). The results indicated that there were no significant differences between the groups in the analyzed variables. The three groups showed improvement in the locomotion score and regression from active to inactive lesion stages. However, at the end of treatment, active lesions were still present in both groups. It was concluded that the proposed 10 days of treatment were insufficient for complete healing of the lesions, suggesting the need to extend the days of application, given the significant regression of the lesions in the established period. More long-term trials are needed to evaluate the effectiveness of copper-zinc chelate spray. RESUMO O objetivo deste estudo foi avaliar a eficácia do spray quelato de cobre-zinco no tratamento de dermatite digital (DD). Foram incluídos 39 membros com lesões de DD de 36 vacas leiteiras, divididos em três grupos: grupo 1 tratado apenas com spray, grupo 2 com spray e bandagem, e grupo 3 com spray e bandagem apenas nos primeiros três dias. As vacas foram avaliadas quanto ao escore de locomoção e à análise qualitativa das lesões no D0 (identificação da lesão e início do tratamento), no D3 (terceiro dia de tratamento), no D7 (sétimo dia de tratamento) e no D10 (décimo e último dia de tratamento). Os resultados indicaram que não houve diferenças significativas entre os grupos nas variáveis analisadas. Os três grupos apresentaram melhora no escore de locomoção e na regressão dos estágios de lesão ativa para inativa. Porém, ao final do tratamento, as lesões ativas ainda estavam presentes em ambos os grupos. Concluiu-se que os 10 dias de tratamento propostos foram insuficientes para a cicatrização completa das lesões, sugerindo necessidade de ampliação dos dias de aplicação, dada a regressão significativa das lesões no período estabelecido. Mais testes de longo prazo são necessários para avaliar a eficácia do spray quelato de cobre-zinco.